POWSZECHNA TAKSACJA NIERUCHOMOŚCI - ISTOTA I ZNACZENIE - Krawczyk, Małgorzata (Wydział Prawa i Administracji UAM, 2009)
The paper focuses on the issue of universal taxation of property. The analysis of Polish solutions is preceded by a short introduction in which individual tax assessment models have been listed. Concepts such as the value of property and the transaction price are presented and their mutual relations described. Different types of the cadastre value that may be used for the purpose of calculation of the taxation base have been identified. The next part of the paper focuses on the cadastre value that will be recognised as the taxation base in Poland. The positive and negative aspects of the mass property valuation that will be binding in Poland in the near future have been analysed. Issues such as representative property, adjustment coefficients, tables, and taxation maps have been discussed, and monitoring of the property market has been recommended. The last part of the paper identifies the modes in which the universal property taxation in Poland may take place. A division between a nationwide and municipal universal property taxation and individual valuation and presentation of the cadastre taxation methods has been made. The paper ends with a conclusion that work on an integrated cadastre system must be finalised soon. It also identifies those areas which still require special attention, and universal property taxation provisions that need to be formulated.
UNIVERSAL TAXATION OF PROPERTY - ESSENCE AND MEANING